IDENTIFYING AND EXPLAINING THE EXECUTIVE TERMINOLOGY ESTABLISHED BY FOREIGN CONSTITUTIONS IN STATES ACKNOWLEDGING A PRESIDENTIAL REGIME - Oana ŞARAMET; I.C. GLIGA (Bulletin of the Transilvania University of Braşov Series VII: Social Sciences • Law • Vol. 7 (56) No. 1 - 2014, 2014)
Identifying the executive, its structure, determining its relationship with the legislative and with the judicial power, identifying the election, designation and appointment procedure for the members of the executive, can be done by determining, based on the constitutional norms of the various states, the political regime establishing the organisation and functioning of its powers. It is also necessary to mention the fact that from the point of view of the form of government, each state has distinctive features with regard to the organising and functioning of powers in the state, to the relationships between them, on the one hand, as well as to the executive, on the other hand
Keywords: executive; political regime; terminology; form of government